Weyl Point and Nontrivial Surface States in a Helical Topological Material - Li, Meize; Liu, Yahong; Du, Lianlian; Zhou, Xin; Song, Kun; Ji, Ruonan; Zhao, Xiaopeng (Frontiers in Materials, 2022)
Topological material has been widely studied in recent years because of excellent physical properties. In this paper, a Weyl topological material composed of the double left-handed helixes is presented. It is demonstrated that the proposed structure possesses a two-dimensional complete topological nontrivial bandgap for a fixed kz in the microwave frequency, and the robust surface states are observed. This unique function provides a promising platform for the development of photonics and electromagnetics.